Az Erzsébet Tudományegyetem alapítása, a pozsonyi és budapesti évek története - Lengvári, István (Per Aspera ad Astra, 2014)
This paper presents the events before the foundation period and the creation of the new law concerning the new universities of Pozsony and Debrecen in 1912. The author describes the first years of the Erzsébet University of Pozsony based on archival sources. The implementation of the plans were roughly destroyed by the events of the First World War and the university was forced to flee to Budapest. There it collaborated with the University Kolozsvár and found temporary operational space before it moved to Pécs in 1923. Fotó: Pécsi Egyetemtörténeti Gyűjtemény